ANALISIS PREFERENSI KONSUMEN TERHADAP PEMBELIAN KOPI DEKAFEINASI GHALKOFF DI BANDAR LAMPUNG - Zakiyah Noor Balqis; Zainal Abidin; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
Decaffeinated coffee is a coffee that has been processed to decrease the caffeine that contained in coffee. Preference analysis is important to do, it help the producer plane the right marketing strategy to win the competition against brands on the market.  The aim of this research are to identify the consumer preference for decaffeinated coffee purchases from the importance level of each attribute and to identify Ghalkoff's decaffeinated coffee attributes are the most considered in purchasing.  The research questionnaire was distributed to 30 samples of respondents from Bandar Lampung using accidental sampling.  The analytical method used to answer the research is conjoint analysis.  The research showed that consumer preferences for purchasing Ghalkoff’s decaffeinated is refer to coffee with the attributes coffee powder sharp and distinctive aroma that has a soft texture coffe powder with affordable price and easily to find and the attribute most considered to purchase the decaffeinated coffee by consumer is aroma. Key words : attributes, decaffeinated, preference.